MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA - Aryana, I Made Putra (Adi Widya: Jurnal Pendidikan Dasar, 2019)
In essence teaching and learning activities are a process of interaction or reciprocal relations between the teacher and students in the learning unit. For this reason, an effort is needed in order to improve the quality of education and teaching, one of which is to choose a strategy or method for delivering learning material so that students can improve their learning achievement. Literature study was conducted to find information about learning, especially the cooperative learning model type Group Investigation (GI). So that by applying the GI cooperative model can improve learning outcomes and student learning motivation. Learning outcomes are what is achieved by students by involving all the potential they have after the students carry out learning activities. Achievement of these learning outcomes can be known by holding an assessment of learning outcomes tests. Motivation to learn means a tendency and high enthusiasm or a great desire for learning. Cooperative learning is a model of teaching where students learn in small groups and have different abilities. Group type Investigation (GI) learning is the most complex learning model. The core steps of the Investigastion Group's learning model are as follows. (1). The teacher forms groups and calls each group leader to receive assignments / material. (2). Each group leader returns to his group and then discusses in depth the tasks that are obtained with the group members. (3). After being considered enough time for group discussion, each group represented by the spokesperson delivered the results of the group discussion that was listened to by all students. (4). The results of the discussion were read by each group alternately by each group until all groups had their turn to deliver the results of the discussion. The application of cooperative learning model group investigation type can be used as one of the learning models in an effort to improve learning outcomes and student motivation in the learning process. Each stage in investigation group learning is a good assessment material related to teacher observation of student activities and the works produced by students while undergoing the learning process.